The construction of meaning by experts and would-be parents in assisted reproductive technology - Silva, Susana (2011)
This article explores the construction of meaning regarding assisted reproductive technology by legal framers, medical practitioners and would-be parents, through the concept of ecology of knowledge. It is argued that these inter-relationships between experts and lay people can be understood in terms of the formation of a social structure of ecology of knowledge, which depends on local and emotional knowledge co-produced by medical doctors, jurists and lay people in dynamic ways without compromising the autonomy of medical, legal and lay knowledge and skills. The assessment of the benefits and risks of assisted reproductive technology partially represents negotiations of knowledge between these social and professional groups, aiming to reproduce existing relations and practices, particularly the social power of medicine and technology, the dominant perceptions about women’s and men’s bodies and the geneticisation of genealogy. These negotiations of knowledge generate new rights, new social actors, new scientific fields and new ways of thinking and talking about individual and institutional responsibilities. Ecology of knowledge comes imbued with hope, trust, power, credibility of institutions and moralisation whereby some citizens’ rights may be weakened.